CONSERVATION AND RESTORATION OF DESERT ECOSYSTEMS - Қушимов Баҳтиёр Алишович (Journals Park Publishing, 2024)
Covering a large portion of the Earth's surface, desert ecosystems face increasing threats, including habitat degradation and desertification. This comprehensive scientific paper explores the multifaceted efforts to conserve and restore these unique and fragile habitats. The study begins by examining conservation strategies such as the establishment of protected areas, sustainable land management practices, and community involvement, highlighting their effectiveness and challenges. Next, it will explore restoration techniques, including revegetation, soil stabilization, water management, and invasive species control, demonstrating their contribution to desertification mitigation and ecosystem function restoration.
Keywords: Desert ecosystems, conservation, restoration, habitats, biodiversity, decertification, climate change, ecosystem services.